Activities of the Medical Commission during the Prophylactic Medical Examination of Athletes - I. A. Vlasova (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Background. Preserving the health of the population, including those involved in sports, is one of the priority directions of the state policy of the Russian Federation. In accordance with the existing legislative and regulatory framework, a system for monitoring the quality and safety of medical care is being implemented in health care institutions, which also applies to medical and physical training services. One of the levels of functioning of such a system is the activity of the medical commission. Intensive training and competitive loads make increased demands on the body and are considered a risk factor for the health of athletes, which serves as the basis for their in-depth medical examination and dispensary observation. Therefore, the primary task of the medical commission during the prophylactic medical examination of athletes is to issue an expert opinion in difficult cases regarding the training and competitive activity of persons with deviations in the state of health.The objective of the research was to study of the activities of the medical commission during the prophylactic medical examination of athletes in the conditions of a medical and physical service on the basis of a scientific analysis of the results of its work for two years.Materials and methods. We studied the medical documentation of athletes who passed the medical commission for two years (2018–2019; n = 82 and n = 81, respectively). The nature of the decisions made and the structure of their reasons were analyzed using the Pearson chi-square test with amendments.Results. The share of positive and negative decisions of the commission, as well as temporary suspension from sports by years, their statistical dependences and the strength of the connection between the results are shown. The stability of the negative conclusions of the commission, as well as the structure of their reasons, was revealed (р ˃ 0.05). At the same time, in the second year of observation, they were more often temporarily suspended from sports due to musculoskeletal system diseases and less often as a result of injuries (p < 0.05).Conclusion. The main regularities of the distribution and formation of expert decisions of the medical commission for the years under study were revealed. The necessity of its activity for the medical and physical training service during the medical examination of athletes is noted, as well as the factors that prevent this are indicated.